Religion in the New Europe - Krzysztof Michalski (Central European University Press, 2006)
The articles in this volume deal with the role of Christianity in the definition of European identity. Europeans often identify advanced civilizations with secularity. But religion is very much alive in other fast developing countries of the world. In Europe, nevertheless, the organized churches very much wanted to stress the Christian character of European identity, and this engendered a lively protest focusing on the perceived threat to the secular European tradition. Also, Europe is facing...